(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article provides an analysis of the modular system of assessment in the higher education system, its history in the world community, its current status. At the same time, the role of this system in the development of knowledge, skills and abilities of students and the opportunities of the education system of Uzbekistan in this area, which needs to be done, are analyzed in detail. The professional development of a person is based on his individual characteristics, as well as the organization of educational content in the form of modules. In this case, each module serves to shape the aspects of the professional activity of the future graduate of higher education. The modular organization of education determines the main content of the credit system.